2016
DOI: 10.1136/bcr-2015-213954
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphataemia due to FGF-23 producing B cell non-Hodgkin's lymphoma

Abstract: Oncogenic osteomalacia (or tumour-induced osteomalacia) is a rare paraneoplastic syndrome caused by overproduction of fibroblastic growth factor 23 (FGF-23) by tumours. Excessive production of FGF-23 can lead to severe, symptomatic hypophosphataemia. The majority of cases have been associated with benign tumours of bone or soft tissue, such as haemangiopericytomas or other neoplasms of mesenchymal origin. We present a case of a 68-year-old woman with an FGF-23 producing B cell non-Hodgkin's lymphoma. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…PMTs are usually small, benign and characterised by low grade and mitotic index, requiring PET imaging to be detected [3]. However, it has also been linked with malignant haematological and solid tumours such as leukaemia [14], head and neck cancer [15], B cell non-Hodgkin's lymphoma [16], sarcoma [17], anaplastic thyroid carcinoma [18], small cell lung cancer [19], prostate cancer [20] and adenocarcinoma of the colon [21].…”
Section: Discussionmentioning
confidence: 99%
“…PMTs are usually small, benign and characterised by low grade and mitotic index, requiring PET imaging to be detected [3]. However, it has also been linked with malignant haematological and solid tumours such as leukaemia [14], head and neck cancer [15], B cell non-Hodgkin's lymphoma [16], sarcoma [17], anaplastic thyroid carcinoma [18], small cell lung cancer [19], prostate cancer [20] and adenocarcinoma of the colon [21].…”
Section: Discussionmentioning
confidence: 99%
“…At a cellular level, dendritic cells and macrophages express FGF23 and increase their production during inflammation (55) and macrophage polarization (30). FGF23 production has also been shown to occur in clonal lymphocytes and plasma cells in patients with B cell neoplasms, including plasma cell dyscrasias (81) and B cell non-Hodgkin's lymphoma (22). In this context, cFGF23 is elevated in circulation, although iFGF23 remains in the normal range in the majority of cases.…”
Section: Fgf23 As a Proinflammatory And Immune-modulatory Hormonementioning
confidence: 99%
“…TIO is an uncommon paraneoplastic syndrome characterized by phosphate wasting attributed to increased circulating FGF23. The syndrome is classically associated with benign mesenchymal tumors; however, recent case reports have associated this syndrome with malignancies, including anaplastic thyroid, colon, and lung carcinomas and diffuse large B cell non-Hodgkin lymphoma [ 11 , 12 ]. One study evaluated FGF23 concentrations in various plasma cell dyscrasias after finding elevated circulating FGF23 in one patient with chronic lymphocytic leukemia and hypophosphatemia, but the authors paradoxically found a weakly positive correlation of FGF23 with serum phosphate in their cohort [ 13 ].…”
Section: Discussionmentioning
confidence: 99%